Endometriosis MR mimickers: T2-hypointense lesions - Edouard Ruaux; Wendaline M. VanBuren; Stéphanie Nougaret; Marie Gavrel; Mathilde Charlot; Flavia Grangeon; Pierre-Adrien Bolze; Isabelle Thomassin-Naggara; Pascal Rousset (Insights into Imaging, 2024)
Abstract Endometriosis is a common crippling disease in women of reproductive age. Magnetic resonance imaging (MRI) is considered the cornerstone radiological technique for both the diagnosis and management of endometriosis. While its sensitivity, especially in deep infiltrating endometriosis, is superior to that of ultrasonography, many sources of false-positive results exist, leading to a lack of specificity. Hypointense lesions or pseudo-lesions on T2-weighted images include anatomical variants, fibrous connective tissues, benign and malignant tumors, feces, surgical materials, and post treatment scars which may mimic deep pelvic infiltrating endometriosis. False positives can have a major impact on patient management, from diagnosis to medical or surgical treatment. This educational review aims to help the radiologist acknowledge MRI criteria, pitfalls, and the differential diagnosis of deep pelvic infiltrating endometriosis to reduce false-positive results. Critical relevance statement MRI in deep infiltrating endometriosis has a 23% false-positive rate, leading to misdiagnosis. T2-hypointense lesions primarily result from anatomical variations, fibrous connective tissue, benign and malignant tumors, feces, surgical material, and post-treatment scars. Key points • MRI in DIE has a 23% false-positive rate, leading to potential misdiagnosis. • Anatomical variations, fibrous connective tissues, neoplasms, and surgical alterations are the main sources of T2-hypointense mimickers. • Multisequence interpretation, morphologic assessment, and precise anatomic localization are crucial to prevent overdiagnosis. • Gadolinium injection is beneficial for assessing endometriosis differential diagnosis only in specific conditions. Graphical Abstract